JURIDICAL REVIEW OF THE CRIME OF AGGRAVATED THEFT COMMITTED CONTINUOUSLY (A STUDY OF DECISION NUMBER 1677/PID.B/2025/PN MDN) - Bonifasius; Tri Reni Novita (CV. Barokah Publsiher, 2026)
aggravated theft committed as a continuing act, to examine the application of the provision on continuing acts (voortgezette handeling), and to analyze the judges’ considerations in rendering a decision in Case Number 1677/Pid.B/2025/PN Mdn. The results of the study indicate that the application of Article 363 paragraph (1) points 4e and 5e of the Indonesian Criminal Code (KUHP) to the defendant’s acts was appropriate, as all elements of the offense of aggravated theft were proven lawfully and convincingly. In addition, the application of Article 64 paragraph (1) of the KUHP concerning continuing acts was also correct, given the existence of unity of intent, similarity of acts, and a relatively short interval between the acts. The judges’ considerations in rendering the decision took into account evidentiary aspects, principles of criminal law, and the objectives of sentencing, such that the decision reflects legal certainty, justice, and utility. Accordingly, Decision Number 1677/Pid.B/2025/PN Mdn can be legally justified.